Pelatihan Implementasi al-Qawa’id al-Sharfiyyah wa al-Nahwiyyah pada Santri Pondok Pesantren Dayah Jamiah Al-Aziziyah dalam Meningkatkan Pemahaman Hukum Islam melalui Kitab Turats - Hanafiah, Mahmudi; M.Nur, Abdullah; Ismuhar, Muhammad; Hidayat, Muhammad; Jannah, Raudhatul; Mardzatillah, Mardzatillah (MEUSEURAYA - Jurnal Pengabdian Masyarakat, 2025)
Classical Islamic texts (kitab turats) serve as primary sources of Islamic law and are relied upon by Muslims around the world. Understanding the manuscripts of these classical works requires adequate foundational knowledge, such as nahwu (Arabic grammar) and sharaf (morphology). However, a purely theoretical study of nahwu and sharaf is often ineffective in uncovering the deeper meanings embedded within the texts. Specialized training in applying the rules of nahwu and sharaf is essential to ensure that the theoretical knowledge gained is not merely passive but instead becomes an active tool in bridging the gap toward comprehending the implicit meanings of kitab turats. Grasping these implicit meanings greatly aids in extracting Islamic legal principles, particularly in addressing contemporary issues.